2019
DOI: 10.1029/2018jc014649
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Ocean Heat Anomalies in the Norwegian Sea

Abstract: Ocean heat content in the Norwegian Sea exhibits pronounced variability on interannual to decadal time scales. These ocean heat anomalies are known to influence Arctic sea ice extent, marine ecosystems, and continental climate. It nevertheless remains unknown to what extent such heat anomalies are produced locally within the Norwegian Sea, and to what extent the region is more of a passive receiver of anomalies formed elsewhere. A main practical challenge has been the lack of closed heat budget diagnostics. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 73 publications
5
51
0
Order By: Relevance
“…Concerning local forcing, the stronger winds lead to stronger heat loss by increasing the turbulent fluxes of sensible and latent heat. Asbjørnsen et al () have recently shown that 50 % of the variability in the Nordic Seas ocean heat content can be attributed to local surface forcing, and although we have not investigated this in depth, we speculate that the changes in heat content arise due to a combination of advection and local forcing. Note that the accelerated Norwegian Current (and resulting greater heat transport from the south) is mainly excluded from the Nordic Seas box shown in Figure .…”
Section: Discussionsupporting
confidence: 92%
“…Concerning local forcing, the stronger winds lead to stronger heat loss by increasing the turbulent fluxes of sensible and latent heat. Asbjørnsen et al () have recently shown that 50 % of the variability in the Nordic Seas ocean heat content can be attributed to local surface forcing, and although we have not investigated this in depth, we speculate that the changes in heat content arise due to a combination of advection and local forcing. Note that the accelerated Norwegian Current (and resulting greater heat transport from the south) is mainly excluded from the Nordic Seas box shown in Figure .…”
Section: Discussionsupporting
confidence: 92%
“…However, this does not rule out that atmospheric circulation anomalies may also have helped to maintain warm ocean temperatures in the Nordic Seas since mid-2000s, resulting in the stagnant period instead of the cooling seen in the SPNA. This may be consistent with conclusions from a recent study by Asbjørnsen et al (2018), which reported that local forcing from air-sea heat fluxes are important for modulating the anomalies on their northward path. Although we have only speculated on the cause for this stagnant period, our simple model of heat convergence reproduced the decadal heat content variability in the eastern Nordic Seas reasonably well, despite the observed disconnection from the SPNA.…”
Section: Connection To the Upstream Subpolar North Atlanticsupporting
confidence: 93%
“…Several observational studies have found that the surface heat flux can only explain a smaller part of the low-frequency variations of the AW heat content in the Nordic Seas (Carton et al, 2011;Skagseth and Mork, 2012;Shi et al, 2017). A study of a physically consistent ocean state estimate also show that surface heat flux is not the main source of AW heat content interannual variability (Asbjørnsen et al, 2018). Although the surface heat flux data is not conclusive, we argue that the surface heat flux is not the main source of the change in decadal trends.…”
Section: Simple Heat Budgetmentioning
confidence: 98%
See 2 more Smart Citations